Susceptibility of Semarang and Purwokerto strains of German cockroach, Blattella germanica (L.) to fipronil, indoxacarb and imidacloprid gel baits - Trisnowati Budi Ambarningrum; Sorta Basar Ida Simanjuntak; Aris Mumpuni; Trisno Haryanto; Eko Puji Sri Haryanto (Penerbit Universiti Kebangsaan Malaysia, 2025)
The susceptibility status of the German cockroach, Blattella germanica (L.), collected from four areas in Semarang and two areas in Purwokerto, Indonesia was investigated to commercial baits containing fipronil, indoxacarb, and imidacloprid, and compared them to the Vector Control Research Unit (VCRU), Universiti Sains Malaysia susceptible strain. The results showed that all German cockroach strains from Semarang had developed resistance to fipronil, indoxacarb, and imidacloprid, while the Purwokerto strains were still susceptible to imidacloprid. The resistance ratio values (RR50) of the Semarang strains to the three insecticides ranged from 1.694 to 8.28 fold (low to moderate resistance). Similarly, the RR50 values for the Purwokerto strains to fipronil and indoxacarb ranged from 2.13 to 3.01 fold (low to moderate resistance), but both Purwokerto strains remained susceptible to imidacloprid, with RR50 values of 0.88 and 0.77-fold, respectively. Based on these findings, it is recommended that insecticide resistance be monitored and that mechanisms and management of resistance be understood. This is crucial for developing effective cockroach management and control strategies.